Pengaruh Cross-Cultural Mentoring dan Cultural Intelligence Terhadap Cross-Cultural Adjustment Mahasiswa IISMA Universitas Padjadjaran - Zahira Salsabila; Dina Sartika (Jurnal Manajemen Bisnis Era Digital, 2024)
Globalization has led to an increasing number of international students. One of the major challenges faced by exchange students is adjusting to a new culture. This study aims to examine the influence of cross-cultural mentoring and cultural intelligence on the cross-cultural adjustment of Padjadjaran University students participating in the IISMA/IISMAVO programs in 2023.This quantitative study, using a descriptive-verificative approach, involved 91 respondents. The results showed that cultural intelligence had a significant positive impact on cross-cultural adjustment. Students with high cultural intelligence were more likely to adapt to new cultural environments. Meanwhile, cross-cultural mentoring alone did not show a significant influence, but when combined with high cultural intelligence, mentoring contributed positively to improving cross-cultural adjustment.This study concludes that developing cultural intelligence is the key to enhancing students' ability to adapt to new cultures. Cross-cultural mentoring can be an effective complement, especially for students with high cultural intelligence. The findings of this study are expected to provide valuable input for the development of pre-departure programs for future exchange students.